Association between nutritional and functional status indicators with caregivers' burden in Alzheimer's disease - de Sousa, OV (2021)
Aim To investigate the association between nutritional and functional status of Alzheimer's disease patients and caregivers' burden. Methods A cross-sectional study was conducted among 79 community-dwelling Alzheimer's disease patients living with their caregivers. Caregivers' burden was assessed using the Zarit Burden-Interview. Multinomial logistic regressions were carried out using caregivers' burden as the dependent variable. Results Caregivers' severe overload was strongly associated with weight loss of more than 3 kg during the previous 3 months (OR = 7.34; 95% CI: 2.02-26.65), lower values of calf girth (OR = 3.20; 95% CI: 1.03-9.93), sarcopenia status (OR = 3.50; 95% CI: 1.09-11.22), and lower gait speed values (OR = 3.83; 95% CI: 1.18-12.47). Otherwise, overweight or obesity (OR = 0.21; 95% CI: 0.05-0.83), was related to lower odds of higher caregivers' burden. Conclusion In community-dwelling older adults with Alzheimer's disease, the nutritional and functional status impairments were strongly associated with increasing caregivers' burden, whereas overweight conferred protection.